EFEKTIVITAS PENDIDIKAN KESEHATAN PADA PASIEN HIPERTENSI STUDI NARRATIVE REVIEW - Onieqie Ayu Dhea Manto; Intan Nur Islamiaty (LPPM Universitas Sari Mulia, 2020)
Background: Hypertension is a serious public health problem. Hypertension has increased every year. Riskesdas data in 2018 reached prevalence (34.1%) in Indonesia and prevalence (44.1%) in South Kalimantan. One of the factors cause hypertension is lifestyle. Lack of the public knowledge about a healthy lifestyle leads to neglect of blood pressure control. This has the potential to cause complications in hypertensive patients. The effort that can be made to prevent and control hypertension are providing health education to hypertensive patients to maintain and improve healthy lifestyle. Objective: To analyze the Effectiveness of Health Education in hypertensive patients. Method: Narrative Review Research Design. The journal criteria used were filtered based on literature titles, abstracts and keywords, namely Health Education + hypertensive patients. Conclusion: Providing health education to hypertensive patients can control blood pressure. Relevant agencies including health offices, hospitals, health centers and health facilities are expected to increase hypertension patient knowledge regarding blood pressure control, for example reducing salt consumption, taking antihypertensive drugs and always checking blood pressure at the health center or other health workers. This can help patients to control their blood pressure.